2000
DOI: 10.1097/00008877-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cocaine-induced sensitization on ethanol drinking: sex and strain differences

Abstract: Sensitization induced by repeated drug exposure has been proposed to increase 'wanting' the drug and to facilitate the transition from moderate to excessive drug intake. The present study examined the effects of cocaine-induced sensitization on ethanol-drinking behavior in male and female rats from different strains. In experiment 1, rats were pretreated with six injections of saline or cocaine (10 mg/kg, i.p.), spaced by 3-day intervals, and were subsequently allowed access to ethanol intake in an unrestricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Indeed, amphetaminesensitized rats were found to consume significantly more ethanol than the saline-treated controls following a 3-month drug-free interval (Fahlke et al, 1994). However, in line with our studies, cocaine-induced sensitization did not modify either the acquisition or the maintenance of ethanol drinking in Wistar-derived hyperactive and hypertensive rat strains (Cailhol and Morme`de, 2000). It remains to be seen whether the discrepancies among the studies are related to differences in methodological issues or in the mechanisms mediating reinforcement from different drugs.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, amphetaminesensitized rats were found to consume significantly more ethanol than the saline-treated controls following a 3-month drug-free interval (Fahlke et al, 1994). However, in line with our studies, cocaine-induced sensitization did not modify either the acquisition or the maintenance of ethanol drinking in Wistar-derived hyperactive and hypertensive rat strains (Cailhol and Morme`de, 2000). It remains to be seen whether the discrepancies among the studies are related to differences in methodological issues or in the mechanisms mediating reinforcement from different drugs.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Cailhol and Mormède [44] reported that SHR rats showed higher levels of cocaine-induced behavioral sensitization when compared to WKHA, but not to WKY, rats. In a subsequent study, the authors reported similar levels of cocaine sensitization for these three strains [45]. On the other hand, repeated MPD treatment (2.5 mg/kg, IP) induced sensitization in SD, but with a weak effect and with no effect in WKY and SHR rats, respectively.…”
Section: Psychostimulantsmentioning
confidence: 71%
“…In adolescent rats, chronic treatment with MPD (0.6, 2.5 and 10 mg/kg, IP) failed to elicit sensitization in SD, WKY and SHR rats [39]. In studies comparing rats of both sexes, SHR females are more sensitive to both the acute effect of psychostimulants and the sensitization produced by these drugs than SHR males [44,45].…”
Section: Psychostimulantsmentioning
confidence: 94%
“…EtOH + cocaine solution enhanced responding for EtOH (Ikegami et al., ). Systemic administration of cocaine resulted in decreased (Uemura et al., ) or had no effect (Cailhol and Mormede, ) on EtOH intake. Collectively, these studies show that cocaine effects on EtOH intake are complex and may vary depending on the experimental protocol.…”
mentioning
confidence: 99%